Biochemical changes after a soccer game in Greek elite soccer players - Bantarakis, A.; Dourountos, I.; Margonis, K.; Nikolaidis, M.; Alexiou, V.; Ispirlidis, I.; Kyparos, I.; Chatzinikolaou, A.; Fatouros, I.; Jamurtas, A. (Inquiries in Sport & Physical Education, 2008)
The purpose of this study was to evaluate the effects of a soccer game on the biochemical profile and the probable time related changes in hepatic and renal function indices. Twenty four players playing in a first division soccer club in Greece were divided into two groups. One group (n=14) was formed by the players that played in the game and the other one by the players that did not play (n=10). Prior to-, immediately-, 24-h and 48-h after the game blood samples were collected to evaluate the levels of the hepatic enzymes aspartic acid aminotransferase (AST) and alanine aminotransferase (ALT). Furthermore, creatinine, urea and ammonia were evaluated. The results revealed significant increases in the levels of AST at 24-h (41%) and 48-h (74%) after the game and in the levels of ALT at 24-h (47%) and 48-h (66%) after the game. Urea and ammonia levels appeared elevated only immediately post-exercise (48% and 47%, respectively) whereas there where no significant changes in the creatinine levels at any point postexercise. These results indicate that a soccer game can result in significant delayed changes in the hepatic enzymes which can be related to muscle damage that can be induced by the game. Furthermore, the increase in urea and ammonia levels immediately after the game could be related to dehydration induced by the game.